Cultivating curious and creative minds the role of teachers and teacher educators, part II - Craig, Cheryl J.; Deretchin, Louise F. (Teacher education yearbook, 2011)
"...the two-volume set examines the cultivation of curious and creative minds. Contributing authors shed light on how this method can be approached in the teaching domain and describe how it plays out in particular situations and contexts."--Back cover.